Quantification of the relative biological effectiveness for ion beam radiotherapy: direct experimental comparison of proton and carbon ion beams and a novel approach for treatment planning - Elsässer, Thilo; Weyrather, Wilma K.; Friedrich, Thomas; Durante, Marco; Iancu, Gheorghe; Krämer, Michael; Kragl, Gabriele; Brons, Stephan; Winter, Marcus; Weber, Klaus-Josef; Scholz, Michael (International journal of radiation oncology, biology, physics, 2010)
Purpose - To present the first direct experimental in vitro comparison of the biological effectiveness of range-equivalent protons and carbon ion beams for Chinese hamster ovary cells exposed in a three-dimensional phantom using a pencil beam scanning technique and to compare the experimental data with a novel biophysical model. - Methods and Materials - Cell survival was measured in the phantom after irradiation with two opposing fields, thus mimicking the typical patient treatment scenario. The novel biophysical model represents a substantial extension of the local effect model, previously used for treatment planning in carbon ion therapy for more than 400 patients, and potentially can be used to predict effectiveness of all ion species relevant for radiotherapy. A key feature of the new approach is the more sophisticated consideration of spatially correlated damage induced by ion irradiation. - Results - The experimental data obtained for Chinese hamster ovary cells clearly demonstrate that higher cell killing is achieved in the target region with carbon ions as compared with protons when the effects in the entrance channel are comparable. The model predictions demonstrate agreement with these experimental data and with data obtained with helium ions under similar conditions. Good agreement is also achieved with relative biological effectiveness values reported in the literature for other cell lines for monoenergetic proton, helium, and carbon ions. - Conclusion - Both the experimental data and the new modeling approach are supportive of the advantages of carbon ions as compared with protons for treatment-like field configurations. Because the model predicts the effectiveness for several ion species with similar accuracy, it represents a powerful tool for further optimization and utilization of the potential of ion beams in tumor therapy.